Motor protection (System protection technology)
The purpose of this module is to familiarize the participant with the features of motor operation and the most common types of protective devices that are installed. Topics include: induction motor characteristics; starting arrangements, torque curves: speed, slip and stall, thermal limits for overload and start-up, thermal and time overcurrent protection, locked rotor, phase fault, ground fault and differential protection. Protection against unbalanced and undervoltage conditions, synchronous motor protection.